Psychophysiological treatment in reduced anxiety with biofeedback training for university students - Vitasari, Prima; Muhammad Nubli, Abdul Wahab; Herawan, Tutut; Suriya Kumar, Sinnadurai (Elsevier Ltd., 2011)
Researchers found some individuals with anxiety disorders, and most of the university's students suffer from some degree of anxiety level during the academic years. Anxiety was prevalent and persistent in student's population. More than half of students with significant symptoms of anxiety do not receive treatment even over two year periods. This research offers a psychophysiological treatment to reduce anxiety through biofeedback training for university students. A total 35 students were participated during 10th sessions training. They are students who have high anxiety level. The psychophysiological arousal was measure used beat-per-minute and breath-per-minute. Repeating measurement of ANOVA was used to evaluate during the 1st session, 4th session, 7th session, and 10th session and further compare the differences. The result shows that there is a significant change over time in the beat-per-minute and breath-per-minute through the participants. From the training, it is shown that after 10th session, students be able to control their heartbeat and respiration to reduce anxiety level. It is concluded that the psychophysiological treatment with biofeedback training is an effective method to reduce anxiety for university students.